Pengalaman terkait kompetensi manajemen pada dokter yang bertugas di daerah tertinggal di Indonesia: studi kualitatif - Fury Maulina; Mardiati Mardiati (Fakultas Kedokteran Universitas Gadjah Mada, 2019)
Experiences related to management competency of doctors in disadvantaged areas in Indonesia: a qualitative studyPurpose: Working in disadvantaged areas is challenging. Geographical barriers, lack of health facilities and accessibility has been impacted to health services delivery which is provided by doctors. This study explored the experiences related to management competency when doctors on duty in disadvantaged areas. Method: We conducted a qualitative study with phenomenological approach in Aceh Singkil Regency (an area in Province of Aceh which is still categorized as disadvantaged areas regarding to Presidential Regulation Number 131 year of 2015). Twelve doctors who work in three different characteristic areas (archipelago, watershed and land areas) underwent in-depth and structured interview. Doctors were recruited purposively. Data were analyzed using thematic analysis. Results: This study reveals that experiences related to management competency is induced by three situations, namely: a) Cultural diversity in community; b) Dealing with difficult situations; and c) Need to survive in difficult areas. Conclusion: Challenges and obstacles which is experienced by doctors when working in disadvantaged areas generate valuable experiences which related to management competencies, as communication skills, cultural competence, creativity, and leadership skills.